Kemampuan Membaca Memahami Teks Berbahasa Jerman - Nurul Amalia Muin; Putri Nurjayana Muin; Hasmawati Hasmawati; Syarifah Fatimah Al Imullah (Phonologie : Journal of Language and Literature, 2023)
Abstract. This research aims to determine the level of reading ability to understand German texts for students of class X IPS SMA Negeri 10 Makassar. analysis using descriptive methods. For data collection, written text is used. The text consists of multiple choice and right and wrong tests. Then the data is analyzed with the percentage technique. The population in this study is class X IPS students at SMA Negeri 10 Makassar, which consists of 3 classes with 93 students. This research stamp is class X IPS 3 students, with as many as 30 selected randomly. The results of this study show that the ability to read and understand the German text of students of grade X IPS 3 SMA Negeri 10 Makassar is included in the excellent category (68.83%).Keyword: Ability, Reading Understanding, Text